2019
DOI: 10.1103/physrevc.99.034320
|View full text |Cite
|
Sign up to set email alerts
|

Tensor-decomposition techniques for ab initio nuclear structure calculations: From chiral nuclear potentials to ground-state energies

Abstract: Background:The computational resources needed to generate the ab initio solution of the nuclear many-body problem for increasing mass number and/or accuracy necessitates innovative developments to improve upon (1) the storage of many-body operators and (2) the scaling of many-body methods used to evaluate nuclear observables. The storing and efficient handling of many-body operators with high particle ranks is currently one of the major bottlenecks limiting the applicability range of ab initio studies with res… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 53 publications
1
26
0
Order By: Relevance
“…However, due to the increasing number of basis states these efforts will require significant computational resources as well as extensive formal developments. To control the increase of computational requirements (memory and runtime), socalled tensor factorization techniques have been proposed recently where high-mode tensors are decomposed into sums of product of lower-rank ones [107,119]. While initial proof-of-principle applications have demonstrated the high potential, extensive additional research is required in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the increasing number of basis states these efforts will require significant computational resources as well as extensive formal developments. To control the increase of computational requirements (memory and runtime), socalled tensor factorization techniques have been proposed recently where high-mode tensors are decomposed into sums of product of lower-rank ones [107,119]. While initial proof-of-principle applications have demonstrated the high potential, extensive additional research is required in this direction.…”
Section: Discussionmentioning
confidence: 99%
“…Here one-and two-body operators are always included in full. However, this is not feasible for three-body interactions due to exponential increase in the number of their matrix elements and therefore 12 these are restricted to e 3max = 16 < 3 e max . The dependence on the basis parameters was tested by computing ground-state observables for different harmonic oscillator frequencies, Ω, and model space sizes, e max .…”
Section: B Model-space Convergencementioning
confidence: 99%
“…Next let us examine rms charge radii r 2 ch 1/2 . In the present approach rms charge radii are computed from rms 12 For what concerns absolute radii, a large variation between the different interactions is observed in all cases. For oxygen isotopes, studies with NN+3N (400) and NNLO sat exist in the literature [16], where was shown that already in these light systems NN+3N (400) leads to a strong underestimation of the size of nuclei.…”
Section: E Charge Radii and Density Distributionsmentioning
confidence: 99%
“…The aforementioned steps make use of prior theoretical knowledge, e.g., to identify desired decoupling patterns in interactions, or define analytical measures for the importance of basis states. If such knowledge is not available, or we want to avoid bias, we can leverage a myriad of Principal Component Analysis (PCA) methods to factorize interactions or intermediate quantities in many-body calculations [271,272]. This can potentially even give us control over the computational scaling of nuclear many-body methods (see, e.g., [273][274][275][276][277]).…”
Section: Leveraging Computational and Algorithmic Advancesmentioning
confidence: 99%